Рост и развитие хомячка серого (Cricetulus migratorius Pall.) - Свириденко, П.А. (Вестник зоологии, 1969)
The growth and development of Cr. migratorius Pall, are observed and described from the day of their birth up to the maturity. Cr. migratorius Pall, are born bare, blind, with closed auricular foramens and accrete fingers. The incisors are seen, but there are no molar teeth. At the age of seven days the body of the animals is covered with hair. On the tenth day the fingers are separated, the molar teeth begin cutting. Being two weeks the animals get a sight and the auricular foramens are opened. At this age they begin eating soft fodder. The Cricetulus migratorius Pall, grow until they reach fifty days.
As to the intensity of growth Cr. migratorius takes the first place among the rodents, followed by Microtus arvalis P a 11., than Clathrionomys S e h r., Apodemus flavicollis M e l c h., Apodemus agrarius Pall, and, at last, by Mus musculus L.
The growth intensity of Cricetulus migratorius is also the highest in comparison with that of other species — Cricetus raddei nigriculus Nehr. and Phodopus sungorus P a 11. (Fig- 3).